Molecular design of peptide amphiphiles for controlled self-assembly and drug release. Issue 15 (26th March 2021) - Liu, Ziqi; Tang, Xuan; Feng, Feng; Xu, Jing; Wu, Can; Dai, Guoru; Yue, Wanqing; Zhong, Wenying; Xu, Keming
Abstract : Peptide amphiphiles with various capping groups and hydrophilic domains were synthesized to control their self-assembling capabilities, that gave nanofibrillar hydrogels for tunable release of doxorubicin. Abstract : Peptide amphiphile-based supramolecular hydrogels hold great promise in drug delivery applications. To cater for a specific drug dose in a demanding biomedical scenario, sophisticated design of peptide amphiphile (PA) molecules is required to tune their self-assembling behaviours as well as drug releasing profiles. Herein, we designed a series of PAs with various capping groups and C-terminal amino acids to systematically optimize their self-assembling capabilities for controlled drug release. First, we evaluated the influence of N-terminal capping groups to find that the 2-naphthylacetyl moiety (Nap) greatly assisted hydrogelation of PAs. Next, self-assembling behaviours of Nap-capped PAs were compared among three candidates that bore varying hydrophilic moieties at the C-terminus (Nap-C12 -VVAAG, Nap-C12 -VVAAD and Nap-C12 -VVAADD, denoted as 1-G, 1-D, and 1-DD). It was found that 1-G and 1-D co-assembled with doxorubicin (DOX) and calcium ions (Ca 2+ ) at a higher efficiency than 1-DD, for 1-G/Ca 2+ /DOX and 1-D/Ca 2+ /DOX hydrogels displayed a dense nanofibrillar network, with lower minimal gelation concentrations and greater storage modulus values. Interestingly, these PA/Ca 2+ /DOX hydrogels exhibited tunable release rates of DOX in vitro, with fast release of DOX found in 1-DD/Ca 2+ /DOX and slow release in 1-G/Ca 2+ /DOX and 1-D/Ca 2+ /DOX. Further cell experiments demonstrated that 1-G/Ca 2+ /DOX and 1-D/Ca 2+ /DOX exhibited higher inhibitory efficacy against HeLa cells, as compared to DOX solution and 1-DD/Ca 2+ /DOX. Finally, PA/Ca 2+ /DOX hydrogels displayed a longer retention time of DOX than aqueous DOX solution in animal experiments, and sustained release of DOX from hydrogels was also evidenced by slow and persisting accumulation of DOX in the major organs of hydrogel-treated mice.